An Accelerated Convergence Algorithm for Sparse-View CT Image Reconstruction. Issue 4 (March 2020) - Wang, Zhao; Liu, Zhiguo; Zhang, Shuang; Pan, Kai; Zhou, Peng; Wang, Xin; Wang, Haoran; Sun, Tianxi
Abstract: In order to reduce radiation dose during CT scanning, sparse sampling is an effective way. Although the TV-based iterative reconstruction algorithm is a breakthrough to solve the problem of sparse-view CT image reconstruction, its applicability is still limited by huge computational burden. It is necessary to study the acceleration method of TV-based iterative algorithm. This paper show that the FISTA acceleration method is not suitable for POCS-TV algorithm, meanwhile, an improved acceleration method, IFISTA, is proposed to accelerate the convergence rate of POCS-TV. Numerical experiments show that the convergence rate of POCS-TV-IFISTA is about 35% faster than POCS-TV.